DESIGN AND FABRICATION OF AN IMPROVED PLANTAIN PROCESSING MACHINE (Nigerian Journal of Technology, 2018)
Nigeria is the largest producer of plantain in West Africa with large percentage of it obtained in the southern part of the country. Plantains are of great nutritional importance, and the proximate analysis reported for plantain shows that per 100g edible portion, plantains contain 67.30 g water, 116 kcal of energy, and 31.15 g of carbohydrate. Although there are several machines that can process plantain but a complete machine that does pulverization, milling, drying, etc. is not readily available in Nigeria. In this research work, an improved plantain processing machine that comprises of all the units was designed and fabricated from available materials in Nigeria. 32kg of plantains were thoroughly peeled, washed, sliced and loaded in the pulverizer unit which pulverized the sliced plantain into paste. The plantain paste was properly dried and ground to obtained plantain flour. Performance evaluation was carried out on the fabricated machine. The results of the performance evaluation show that force, torque, and power of 320N, 33.60Nm, and 2533.7088W were required for operation of the machine. Furthermore, the total mass of flour produced from 32kg of plantain was 4.29kg. It was observed that mass of water in 32kg of plantain was 19.25kg. The total mass of plantain pulp after addition of 5kg of water was 37kg. These values were used to determine the percentage composition of water in the pulverized plantain pulp which was obtained as 65.54%.  Besides, the efficiency of the machine and machine throughput capacity were obtained as  http://dx.doi.org/10.4314/njt.v37i3.14Plantain, Processing machine, Design, Fabrication, Flour, Pulverizer